A new species of Vriesea Lindl. (Bromeliaceae) from the Atlantic Rainforest of São Paulo State, Brazil - Martins,Suzana Ehlin (2021)
ABSTRACT A new species of Vriesea Lindl. is described and illustrated. Vriesea altobocainensis is only known for the Atlantic Forest of Serra da Bocaina. It is a robust epiphyte, characterized by a reddish inflorescence, and floral and primary bracts with an orbicular and broadly ovate shape; morphologically, it is close to Vriesea altodaserrae L.B.Sm. and Vriesea sceptrum Mez. However, the new species can be distinguished from these others mainly for the color, dimensions and shape of floral and primary bracts, number of inflorescence branches and number of flowers per branch.